Transmission of Zika virus through breast milk and other breastfeeding-related bodily-fluids: A systematic review - Colt, Susannah; Garcia-Casal, Maria N.; Peña-Rosas, Juan Pablo; Finkelstein, Julia L.; Rayco-Solon, Pura; Weise Prinzo, Zita C.; Mehta, Saurabh (PLOS Neglected Tropical Diseases, 2017)
Author summary Zika virus (ZIKV) infection was considered a mild fever illness until the recent and ongoing outbreak in South America revealed that the virus can cause microcephaly and other neurological disorders. ZIKV is primarily transmitted by mosquitoes, but can also spread from person to person through sex, blood transfusion, and from mother to child during pregnancy or delivery. It is unknown if ZIKV can spread from mother to child during breastfeeding. We conducted a systematic review of the literature to summarize evidence of ZIKV transmission via breastfeeding and the presence ZIKV in breast milk. Our search resulted in 2 case reports that described 3 mothers and their newborns. ZIKV was confirmed in the blood and breast milk of all 3 mothers and in the blood of 2 newborns. More evidence is needed to confirm if ZIKV is transmitted via breastfeeding.